Francuski Kodeks procedury cywilnej z 1806 roku - kodeks Napoleona Bonaparte czy Ludwika XIV? - Klimaszewska, Anna (Czasopismo Prawno-Historyczne, 2018)
The French Code of Civil Procedure of 1806 remained binding on the Polish territories for about 70 years and it exerted a significant influence on, among others, the shaping of the contemporary Polish terminology in this area. The present publication analyzes the issue of the nature of Code de procédure civile which – despite the extremely strong pressure during the French Revolution to introduce drastic change in the court procedure – in large part reproduced the solutions put forward in the ordinance by Louis XIV from April 1667 (Ordonnance civile touchant la réformation de la justice). On its basis, this branch of the law had been already codified in 17th century. Thus Code de procédure civile was certainly not the first code pertaining to civil procedure in France. Furthermore, the extent of the borrowings described in the article justifies the assumption that it was more of an amendment to the 1667 ordinance rather than a separate codification.